LFC in interconnected power system via Internal Model Control Scheme and Model-Order Reduction - Reddy, A. VijayaKumar; Salma, U. (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
An interconnected power systems are subjected to performance gradual decline due to sudden small load perturbations, structural variations, parameter uncertainties, etc. The LFC objective is to maintain the balance of the area generation-demand by adjusting the obtained outputs on regulating units in response to the frequency and tie line power deviations. The state of the system changes, as the demand varies from its normal operating value. The internal model control (IMC) scheme, which includes the concept of model-order reduction and modified IMC filter design is discussed. For model reduction, the combination of Particle Swarm Optimization (PSO) and Dominant Pole Retention technique is proposed. The concept is that a lower order is placed in place of full order of the system for internal model control. In this the performance to counteract load disturbances can be achieved by using improved closed loop system.